Linux for Embedded and Real-time Applications (3rd Edition) - Abbott, Doug (Elsevier, 2013)
This new edition of Linux for Embedded and Real-Time Applications provides a practical introduction to the basics and the latest developments in this rapidly evolving technology. Ideal for those new to using Linux in an embedded environment, it takes a hands-on approach and covers key concepts plus specific applications. Key features include:Substantially updated to focus on a specific ARM-based single board computer (SBC) as a target for embedded application programmingIncludes an introduction to Android programming With this book you will learn:The basics of Open Source, Linux and the embedded spaceHow to set up a simple system and tool chainHow to use simulation for initial application testingNetwork, graphics and Android programmingHow to use some of the many Linux components and toolsHow to configure and build the Linux kernel, BusyBox and U-Boot bootloaderProvides a hands-on introduction for engineers and software developers who need to get up to speed quickly on embedded Linux, its operation and its capabilities - including AndroidUpdated and changed accompanying tools, with a focus on the authors specially-developed Embedded Linux Learning Kit